Voltage gated sodium channels in cancer and their potential mechanisms of action. Issue 1 (1st January 2019) - Angus, Madeline; Ruben, Peter
ABSTRACT: Voltage gated sodium channels (VGSC) are implicated in cancer cell invasion and metastasis. However, the mechanism by which VGSC increase cell invasiveness and probability of metastasis is still unknown. In this review we outline lesser known functions of VGSC outside of action potential propagation, and the current understanding of the effects of VGSC in cancer. Finally, we discuss possible downstream effects of VGSC activation in cancer cells. After extensive review of the literature, the most likely role of VGSC in cancer is in the invadopodia, the leading edge of metastatic cancer cells. Sodium gradients are used to drive many biological processes in the body, and invadopodia may be similar. The function of the sodium hydrogen exchanger (NHE) and sodium calcium exchanger (NCX) are driven by sodium gradients. Voltage gated calcium channels, activated by membrane depolarization, are also capable of becoming activated in response to VGSC activity. Changes to hydrogen ion exchange or calcium handling have functional consequences for invadopodia and would explain the relationship between VGSC expression and invasiveness of cancer cells.